PARANEOPLASTIC SYNDROMES - Suega, Ketut (journal of internal medicine, 2012)
The term Paraneoplastic Syndromes (PNS) refers to symptoms or signs resulting from damage to organs or tissues that are remote from the site of a malignant neoplasm or its metastases. Widely known examples include cancer cachexia, hypercalcemia,Cushing!s syndrome,and Trousseau!s syndrome . A particularly devastating form of paraneoplastic syndromes ia a group of disorders classiÞ ed as Paraneoplastic Neurological Disorders (PND).The incidence of PNS varies with the neurological syndrome and with the tumor. PNS can occurs in 7 to 10% of all patients with cancer. A paraneoplastic syndrome may result from production and release of antibodies and physiologically active substances, or it may be idiopathic. However, not all paraneoplastic syndromes are associated with these antibodies. Symptoms can be atypical, psychiatric, or even ß uctuating, and PNS should often be in the differential diagnosis of otherwise unexplained neurological syndromes. An international panel of neurologists has established diagnostic criteria that divide patients with a suspected PNS into deÞ nite and probable categories. These criteria are based on the presence or absence of cancer, the presence of well-characterized antibodies, and the type of clinical syndrome. Detection of a "well-characterized# paraneoplastic antibody is extremely helpful because it proves the paraneoplastic etiology of the neurological syndrome. Usually, the paraneoplastic syndromes are divided into the following categories: (1) miscellaneous (nonspeciÞ c), (2) rheumatologic, (3) renal, (4) gastrointestinal, (5) hematologic, (6) cutaneous, (7) endocrine, and (8) neuromuscular. Treatment varies with the type and location of the paraneoplastic disorder, consist of treatment of the underlying tumor, as well as the treatment of the presumptive immune-mediated disorder is based on immunosuppression. Because paraneoplastic syndromes differ widely from individual to individual, prognosis may vary greatly.
Keywords: paraneoplastic syndrome, paraneoplastic neurological disorders, well-characterized antibodie